-0.7(4y-3)+2.3y=-0.3y+2.1

Simple and best practice solution for -0.7(4y-3)+2.3y=-0.3y+2.1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.7(4y-3)+2.3y=-0.3y+2.1 equation:


Simplifying
-0.7(4y + -3) + 2.3y = -0.3y + 2.1

Reorder the terms:
-0.7(-3 + 4y) + 2.3y = -0.3y + 2.1
(-3 * -0.7 + 4y * -0.7) + 2.3y = -0.3y + 2.1
(2.1 + -2.8y) + 2.3y = -0.3y + 2.1

Combine like terms: -2.8y + 2.3y = -0.5y
2.1 + -0.5y = -0.3y + 2.1

Reorder the terms:
2.1 + -0.5y = 2.1 + -0.3y

Add '-2.1' to each side of the equation.
2.1 + -2.1 + -0.5y = 2.1 + -2.1 + -0.3y

Combine like terms: 2.1 + -2.1 = 0.0
0.0 + -0.5y = 2.1 + -2.1 + -0.3y
-0.5y = 2.1 + -2.1 + -0.3y

Combine like terms: 2.1 + -2.1 = 0.0
-0.5y = 0.0 + -0.3y
-0.5y = -0.3y

Solving
-0.5y = -0.3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '0.3y' to each side of the equation.
-0.5y + 0.3y = -0.3y + 0.3y

Combine like terms: -0.5y + 0.3y = -0.2y
-0.2y = -0.3y + 0.3y

Combine like terms: -0.3y + 0.3y = 0.0
-0.2y = 0.0

Divide each side by '-0.2'.
y = 0

Simplifying
y = 0

See similar equations:

| 8k-7=11-2k | | 7y-5x=29 | | 2(3x+2)-3=x-39 | | 35+146-1=180 | | 4y-18=3(2y-4) | | d/dx(sin(2)x) | | -5(10)+7y=-15 | | 3x=-7+y | | 6y-4y=16+2y | | (6x-5)+8=2(x-5) | | x^2-1/81=0 | | t^3-5t^2+3t=0 | | 6-4y=16+2y | | 1/3x=-2/5=-6/5 | | -200-x=103/2x | | 6x-4y=16+2y | | 8x-3=2x+10 | | 4(2y-3)+6(3-y)=22 | | 17+4x-1x= | | -5+7y=-15 | | 4x=x-32 | | 12x=9x-12 | | 3(1-1y)=24-1y | | 3(3x-2)=7x+4 | | 5=6+a | | 5x+24x= | | 4x-3=2x+10 | | 48=3(x+8) | | y-3=-9 | | 5(7x+5)=130 | | 6x+3y=24+1y | | 5x-2(-8)=6 |

Equations solver categories